Analysis of the protective effects of γ-aminobutyric acid during fluoride-induced hypothyroidism in male Kunming mice. (1st January 2019) - Yang, Haoyue; Xing, Ronge; Liu, Song; Yu, Huahua; Li, Pengcheng
Abstract: Context: Compounds to treat hypothyroidism in the absence of cardiac side effects are urgently required. In this regard, γ-aminobutyric acid (GABA) has gained interest due to its anti-anxiolytic, antihypertensive and antioxidant properties, and reported benefits to the thyroid system. Objective: We investigated the ability of GABA to ameliorate fluoride-induced thyroid injury in mice, and investigated the mechanism(s) associated with GABA-induced protection. Materials and methods: Adult male Kumning mice ( N  = 90) were exposed to NaF (50 mg/kg) for 30 days as a model of hypothyroidism. To evaluate the effects of GABA administration, fluoride-exposed mice received either thyroid tablets, or low (25 mg/kg), medium (50 mg/kg) or high (75 mg/kg) concentrations of pure GABA orally for 14 days groups ( N  = 10 each). The effects of low (50 mg/kg); medium (75 mg/kg) and high (100 mg/kg) concentrations of laboratory-separated GABA were assessed for comparison. Effects on thyroid hormone production, oxidative stress, thyroid function-associated genes, and side-effects during therapy were measured. Results: GABA supplementation in fluoride-exposed mice significantly increased the expression of thyroid TG, TPO, and NIS ( P  < 0.05), significantly improved the thyroid redox state ( P  < 0.05), modulated the expression of thyroid function-associated genes, conferred liver metabolic protection, and prevented changes to myocardial morphology, thus reducing side effects. Both pure and laboratory-separated GABA displayed comparative protective effects. Discussion and conclusion: Our findings support the assertion that GABA exerts therapeutic potential in hypothyroidism. The design and use of human GABA trials to improve therapeutic outcomes in hypothyroidism are now warranted.